Towards expeditious justice a policy analysis of the law's delay - Public Administration 248 Second Semester 1980-1981 (Philippine Journal of Public Administration, 1981)
Judicial delay means the waiting time endured by litigants beyond the minimum period required by due process. It is the unnecessary prolongation of a law suit, resulting from a huge volume of cases and from the "drag" in case processing. The trend of congestion is alarming, with the pending cases already in the half-million mark. Socio-economic forces and poor service capability of the court system jointly account for the continuous increase of pending cases. With the present rates of disposition, the number of incumbent judges is inadequate to dispose of cases to meet the demand posed by cases filed and cases pending. Postponements in the trial courts were found to occur mostly at the trial stage and to be largely caused by lawyers/fiscals. The barangay courts have been found to be effective in that they were able to settle 80 percent of cases submitted to them and only 12 percent go to the regular courts. With these findings considered, the model for judicial delay suggests courses of action that would screen out unnecessary suits and speed up the disposition of cases. How to keep out the unnecessary and non-jurisprudential cases from the court system, and how to accelerate case disposition without sacrificing due process are, therefore, the twin aspects of judicial delay that must be addressed by policies.